Angiosarcoma of the Auricle in a Patient with Xeroderma Pigmentosum Variant - Masazumi Onishi; Kanako Tsunoda; Fumihiko Maeda; Shinichi Moriwaki; Hiroo Amano (Karger Publishers, 2020)
Xeroderma pigmentosum (XP) is an inherited autosomal recessive disorder characterized by photosensitivity and an increased risk of developing multiple skin neoplasms at sites exposed to the sun. We report a 73-year-old Japanese man with angiosarcoma of the auricle and an XP-variant, which is a very rare condition. In this case, long-term physical stimulation due to auricular deformation after surgery may have been the cause. Angiosarcoma associated with XP has a better prognosis than common angiosarcoma, perhaps because of the smaller tumor size. As XP patients are at high risk of skin neoplasms, they consult dermatologists regularly, and therefore skin tumors are likely to be detected early.